Asteroid debris: Temporary capture and escape orbits. (November 2016) - Vetrisano, Massimo; Celletti, Alessandra; Pucacco, Giuseppe
Abstract: We investigate the dynamical behaviour of debris ejected from the surface of an asteroid, due to a generic – natural or artificial – surface process. We make an extensive statistical study of the dynamics of particles flowing from the asteroid. We observe different behaviours: particles which fall again on the asteroid surface, or rather escape from its gravitational field or are temporary trapped in orbit around the asteroid. The tests are made by varying different parameters, like the size of the asteroid, its eccentricity, the angular velocity of the asteroid, the area-to-mass ratio of the debris. We also extend the study to the case of a sample of binary asteroids with a mass ratio equal to 10 −3 ; we vary the distance of the moonlet from the asteroid, to see its effect on the debris dynamics. Our simulations aim to identify regions where the debris can temporarily orbit around the asteroid or rather escape from it or fall back on the surface. These results give an important information on where a spacecraft could be safely stay after the end of the process which has produced the debris. Abstract : Highlights: Debris evolution from the surface of a single or binary asteroid is analysed. Debris falls on the asteroid surface, escapes its proximity or orbits temporarily. The timescale depends on the asteroid's kinematics and particles area-to-mass ratio. Regions where spacecraft can safely avoid debris after some time are identified.